Extension of ustekinumab maintenance dosing interval in moderate‐to‐severe psoriasis: results of a phase IIIb, randomized, double‐blinded, active‐controlled, multicentre study (PSTELLAR). (16th November 2017) - Blauvelt, A.; Ferris, L.K.; Yamauchi, P.S.; Qureshi, A.; Leonardi, C.L.; Farahi, K.; Fakharzadeh, S.; Hsu, M.‐C.; Li, S.; Chevrier, M.; Smith, K.; Goyal, K.; et al.
Summary: Background: Phase III studies showed that some patients maintained response for ≥ 6 months following ustekinumab discontinuation. Objectives: To assess clinical responses with extended ustekinumab maintenance dosing intervals. Methods: Adults with moderate‐to‐severe plaque psoriasis received ustekinumab at weeks 0, 4 and 16 during open‐label treatment. Patients achieving a week‐28 Physician's Global Assessment (PGA) score of cleared/minimal (PGA = 0/1) were randomized 1 : 4 to group 1 [approved every 12 weeks (q12 wk) maintenance] or group 2 (q12–24 wk; response‐based dosing determined by time to loss of PGA = 0/1). Key end points included the number of visits with PGA = 0/1 (primary end point) and ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) between weeks 88 and 112, and PGA/PASI responses between weeks 28 and 112. Results: Overall, 378 patients achieved PGA = 0/1 at week 28 and were randomized to group 1 ( n  =   76) or group 2 ( n  =   302). Patients in group 1 had numerically greater mean numbers of visits with PGA = 0/1 than group 2 and also with PASI 75 from week 88 to 112. A higher proportion of patients in group 1 (55%) than group 2 (39%) had PGA = 0/1 at all seven visits from week 88 to 112. Maintenance of response was observed with dose‐interval extension beyond q12 wk in a subset of patients. Extending the dosing interval did not affect antibody development or safety. Conclusions: Efficacy was better maintained among week‐28 PGA responders randomized to continue q12 wk ustekinumab vs. extending maintenance dosing based on clinical response, although some patients maintained high levels of efficacy with up to q24 wk dosing. Abstract : What's already known about this topic? Ustekinumab maintenance doses are typically administered every 12 weeks, although earlier studies and clinical practice suggest that some patients may maintain high levels of efficacy with extended dosing intervals. What does this study add? Patients better maintained higher levels of efficacy when ustekinumab was given every 12 weeks compared with longer dosing intervals. A subset of patients, however, continued to achieve high levels of efficacy with dosing intervals as long as every 24 weeks. Overall, these findings further our understanding of clinical response to ustekinumab in patients with moderate‐to‐severe psoriasis. Respond to this article